Organizational Culture and Innovation: A Conceptual Framework - Mohd Yunus Majid; Kamal Rizwan Mahadzir; Faridah Maarof (International Journal of Management and Data Analytics)
Organizational culture is important in a business organization because it influences the action and approaches in conducting the business effectively in highly competitive and rapidly changing environments. Moreover, innovative culture has been recognized as one of the crucial elements in achieving competitive advantage and sustainable growth. The study attempts to bridge the gap by means of a quantitative survey methodological research that explores the influence and relationship between organizational culture and innovation using the all-inclusive and practical-based framework of organizational culture, especially in the context of a Malaysian company. The scope of the study is specifically aimed at executives in one of Malaysian largest utility companies in Malaysia. The organizational culture studied in this research centered on the Denison Organizational Culture Model, which demonstrates the influence of the cultural traits of Involvement (Empowerment, Team Orientation, and Capability Development) and Adaptability (Creating Change, Customer Focus, and Organizational Learning) towards Innovation. This causal study employs quantitative methodology which gathers primary data collected from more questionnaire surveys conducted among executives using mail and electronic survey system. A number of statistical tests were conducted which are socio-demographic analysis, descriptive analysis, correlation test, and multiple regression analysis to analyze and describe the findings and to examine the research questions and hypothesis. A total of six hypotheses will be developed to find the relationship between culture and innovation in the organization. Creating change, which contributes significantly toward organizational innovation may serve as a good reference for organizations in strategy prioritization and operational execution.